2016
DOI: 10.1111/jssr.12252
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Image of God: God as Reality and Psychological Well‐Being

Abstract: Research has widely demonstrated that religiosity is related to psychological well

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
(55 reference statements)
2
29
0
1
Order By: Relevance
“…Distal defences often involve existential reflection on the meaning of finitude and the construction of cultural apparatuses that allow individuals to give meaning to their lives and actions. Religions, for example, are very important in this area because they make it possible to envisage individual existence beyond earthly life and beyond death [ 3 , 4 ]. However, these systems are fragile because they are constantly being questioned by common and rational thought [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Distal defences often involve existential reflection on the meaning of finitude and the construction of cultural apparatuses that allow individuals to give meaning to their lives and actions. Religions, for example, are very important in this area because they make it possible to envisage individual existence beyond earthly life and beyond death [ 3 , 4 ]. However, these systems are fragile because they are constantly being questioned by common and rational thought [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This instrument quantifies the strength of associations between concepts by comparing response latencies when people categorize stimuli (Greenwald, McGhee, & Schwartz, 1998). The IAT is also the implicit measure that has been used most frequently to study religious cognition (Jong et al, 2017), and at least eight studies have adapted the IAT to measure supernatural belief (Dentale et al, 2018;Farias et al, 2017;Irwin, 2014;Jong et al, 2012;Lindeman, Svedholm-Hakkinen, & Riekki, 2016;Shariff, Cohen, & Norenzayan, 2008;Testoni, Visintin, Capozza, Carucci, & Shams, 2016;Turpin, Andersen, & Lanman, 2018). 1 For example, using a "single target" variant of the IAT (Bluemke & Friese, 2007;Wigboldus, Holland, & van Knippenberg, 2006), Shariff et al (2008) found that the strength of the association between supernatural entities (e.g., god, devil, heaven) and terms associated with "truth" (e.g., actual, genuine, real) was positively associated with self-reported religiosity measures, especially the item "I believe in God".…”
Section: The Implicit Association Test (Iat)mentioning
confidence: 99%
“…As affirmed by Terror Management theory, awareness of death is inevitable, and such awareness may occur at any moment for uncontrollable reasons and generate a feeling of latent and constant terror [2]. Anguish linked to death can be managed through supportive cultural systems, which may include symbolic practices, allowing us to envisage salvation after death [3,4].…”
Section: Introductionmentioning
confidence: 99%